The Concept of Thermodynamic Law in The Perspective of Islamic Philosophy - Eko Nopriyansa; Dhyanesh Revi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This article aims to analyze the concept of thermodynamic laws in physics through the lens of Islamic philosophy, particularly in relation to the concept of Tawhid or divinity. The analysis focuses on identifying the intersections and contrasts between the principles of thermodynamics and the Islamic concept of Tawhid, especially in explaining the existence and nature of energy. This research is a literature-based study utilizing secondary data obtained through an extensive review of scholarly texts and relevant literature. The findings indicate that there is both convergence and divergence between the empirical understanding of thermodynamic laws and the Islamic concept of Tawhid. For instance, the first law of thermodynamics, emphasizing the conservation of energy, aligns with certain philosophical interpretations of Tawhid. However, contrastingly, Surah Al-Ikhlas underscores the uniqueness and incomparability of Allah, affirming that nothing can equate to Allah in meaning or substance, thereby distinguishing the concept of divine energy from empirical understandings. This study contributes to the discourse on the integration of science and religion by providing a philosophical framework to explore how scientific principles can intersect with Islamic theological concepts. It highlights the potential for dialogue between empirical evidence and absolute belief, fostering a deeper understanding of both domains.